Ten‐year follow‐up results of a randomized clinical trial comparing left thoracoabdominal and abdominal transhiatal approaches to total gastrectomy for adenocarcinoma of the oesophagogastric junction or gastric cardia. Issue 4 (21st January 2015) - Kurokawa, Y.; Sasako, M.; Sano, T.; Yoshikawa, T.; Iwasaki, Y.; Nashimoto, A.; Ito, S.; Kurita, A.; Mizusawa, J.; Nakamura, K.; for the Japan Clinical Oncology Group (JCOG9502)
<x xml:space="preserve">Abstract</x> Background The optimal surgical approach for treatment of oesophagogastric junction (OGJ) cancer is controversial. A randomized clinical trial (JCOG9502) comparing transhiatal (TH) and left thoracoabdominal (LTA) approaches was stopped after the first interim analysis owing to limited efficacy for LTA resections. Complete 10‐year follow‐up data are now available. Methods Patients with histologically proven adenocarcinoma of the OGJ or gastric cardia with oesophageal invasion of 3 cm or less were randomized to a TH or LTA approach. Both groups underwent total gastrectomy and splenectomy with D2 nodal dissection plus para‐aortic lymphadenectomy above the left renal vein. For LTA, a thorough mediastinal lymphadenectomy below the left inferior pulmonary vein was also mandatory. The primary endpoint was overall survival. Results A total of 167 patients (82 TH, 85 LTA) were enrolled. The 10‐year overall survival rate was 37 (95 per cent c.i. 26 to 47) per cent for the TH approach and 24 (15 to 34) per cent for the LTA technique (P = 0·060). The hazard ratio for death was 1·42 (0·98 to 2·05) for the LTA technique. Subgroup analysis based on the Siewert classification indicated non‐significant survival advantages in favour of the TH approach. Conclusion LTA resections should be avoided in the treatment of adenocarcinoma of the OGJ or gastric cardia. Registration number: NCT00149266 (https://www.clinicaltrials.gov).